Effects of Sleep Deprivation on Psychological Behavior of Bsit Students: Toward a Guide (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The main focus of this research was to obtain an insight into the effects of sleep deprivation on the psychological behavior of Bachelor of Science in Information Technology Strand students, S.Y. 2019–2020. This study used the descriptive method. The instruments used by the researcher in this study were the questionnaires, unstructured interviews, and focused group discussions. Sleep deprivation refers to a condition wherein an individual does not get a proper and enough amount of sleep. Sleep deprivation can affect the psychological behavior of a student. Less than 8 hours of sleep at night may alter the human body and mind. This alteration or change has a huge impact on the life of the student. The purpose of this study was to analyze and confirm the extent to which sleep deprivation affects a student correlated with the following variables: attention, decision-Making, and mood. A survey was conducted with 50 Information Technology students in Bestlink College of the Philippines, S.Y. 2019–2020. The respondents will answer questions that correspond to our variables. Based on the data gathered, the effect on the respondents' attention was moderate. The students who are good listeners ranked first, with a weighted mean of 3.44. In terms of decision making, theeffect on the respondents was also moderate, with a weighted mean of 3.42 for rank 1 and an overall weighted mean of 3.30. In terms of the variable mood, the weighted mean was 3.56, which indicated that insufficient sleep has a high effect on their positive thoughts. In the third part of the questionnaire, the researchers asked the respondents to choose the advantage and disadvantages of sleep deprivation. The results showed a moderate effect on the respondents to recall of their daily routine, with a weighted mean of 3.12. In terms of decision making, the respondents who decide in a deliberately logical weighted ranked first and a weighted mean of 3.10 with the weighted mean overall of 3.04 and verbally interpreted as a moderate effect. For the mood variable, the effect was high on a respondent who felt relaxed after a good sleep, which ranked first, with the overall weighted means of 3.52 and 3.33. This study seeks to understand the unique relationship between sleep deprivation and psychological behavior to understand how sleep deprivation influences psychological behavior for individuals to realize the importance of consistent, restful sleep.
Keywords: sleep deprivation